PENENTUAN PRIORITAS PILIHAN MAHASISWA DALAM PEMILIHAN LOKASI PERGURUANTINGGI DENGAN ANALISIS CONJOINT - MAXSI ARY (Paradigma, 2015)
A private college is education marketers that need to identify students for educational products; educational products develop and implement a promotion to attract attention and give a strong response from prospective students. Advantages of private college to attract more students improved. The aim of this study is to analyze the preferences of students from the Department of Information Management AMIK Bandung BSI in choosing the campus. Research preferences in choosing college students conducted by applying conjoint analysis using SPSS 17.0. How that is done is to obtain a score of uses that can represent every aspect of campus services owned factor, so that on that score can be deduced about what attributes are most considered by the students in choosing a college. Results of the respondents preference highest-value is a factor field (14.92%), curriculum (13:21%), accreditation (12.75%), lecturer (12:13%), building (11.96%), library (11.87%), Distance (11.66%) and advertising (11:46%). Results of the aggregate utility level factors/attributes chosen by respondents, that the respondents liked the selection of educational services in the campus is having a field campus, open curriculum (the administration delivered in advance at the beginning of registration), the campus has been accredited, senior lecturer option, the size of ordinary buildings (less noticed), the library has a large collection of books, the distance between the house and near the campus, and advertising less attention.